Reflections on self‐determination theory as an organizing framework for personality psychology: Interfaces, integrations, issues, and unfinished business. Issue 1 (4th December 2018) - Ryan, Richard M.; Soenens, Bart; Vansteenkiste, Maarten
Abstract: Objective: This special issue focuses on self‐determination theory (SDT) as an integrative framework for the wider field of personality research. In this commentary our aims include: reflecting on the utility and strengths of SDT as such a general framework and responding to the various contributions in this issue regarding their use of SDT as a guiding, complementary, or contrasting framework. Methods and Results: We describe how SDT has developed organically and conservatively from "within" based on the emerging patterns of evidence, as well through the ongoing challenges from other models and frameworks. We then discuss each of the various contributions to this special issue, addressing themes that include SDT's breadth of methods, and its relevance to topics such as narcissism, wisdom, individual differences, Big‐Five traits, and the neuropsychology of motivation, among others. Across these discussions, we highlight fruitful avenues for research and cross‐fertilization across the fields of personality, development, motivation, and neuroscience. At the same time, we counter some claims made about SDT, and forward certain cautions regarding the integration of SDT and other personality frameworks and models. Conclusions: We conclude by revisiting the value of broad theory, and SDT in particular, for coordinating complex research findings concerning motivation, personality development and wellness across multiple levels of analysis and, perhaps more importantly, for pointing researchers to the right questions within today's prolific empiricism.